2009
DOI: 10.1086/597097
|View full text |Cite
|
Sign up to set email alerts
|

Proof of Activity with AMD11070, an Orally Bioavailable Inhibitor of CXCR4‐Tropic HIV Type 1

Abstract: These results demonstrate the activity of AMD11070, the first oral CXCR4 antagonist, against X4-tropic HIV-1. The drug was well tolerated, with no serious safety concerns. AMD11070 is on clinical hold because of histologic changes to the liver observed in long-term animal studies; additional preclinical safety assessments are pending.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
54
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 28 publications
1
54
0
Order By: Relevance
“…A majority of the subjects dosed with 200 mg twice daily attained plasma concentrations at or near the in vitro 90% effective concentration 24 h after dosing. The combined results of two related 10-day phase II studies of HIV-infected subjects receiving 200 mg AMD070 twice daily demonstrated an antiviral effect, defined as a 1-log reduction in X4 relative luminescence units in the profile assay, in 7 of 15 subjects (13,17). Furthermore, like its predecessor, AMD3100, AMD070 showed a dose response for leukocytosis which may serve as a surrogate marker for CXCR4 inhibition and a second potential indication for use of the drug.…”
mentioning
confidence: 98%
“…A majority of the subjects dosed with 200 mg twice daily attained plasma concentrations at or near the in vitro 90% effective concentration 24 h after dosing. The combined results of two related 10-day phase II studies of HIV-infected subjects receiving 200 mg AMD070 twice daily demonstrated an antiviral effect, defined as a 1-log reduction in X4 relative luminescence units in the profile assay, in 7 of 15 subjects (13,17). Furthermore, like its predecessor, AMD3100, AMD070 showed a dose response for leukocytosis which may serve as a surrogate marker for CXCR4 inhibition and a second potential indication for use of the drug.…”
mentioning
confidence: 98%
“…Proof of concept that AMD070 (originally referred to as AMD11070) can selectively inhibit X4-tropic virus in HIV-1-infected patients was provided by Saag and colleagues [54] and Moyle and colleagues [55]. Like AMD3100, AMD070 induced a dose-related elevation of the WBC counts, which can be attributed to CXCR4 blockade.…”
mentioning
confidence: 99%
“…AMD070 (also known as AMD11070), which has two aromatic rings in addition to a primary and a tertiary amine, has an IC 50 of 2 to 26 nM against an X4 HIV strain and is orally bioavailable (22,29).…”
mentioning
confidence: 99%